2022
DOI: 10.1097/txd.0000000000001390
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Transplantation of the Full-length Porcine Intestine After Normothermic Machine Perfusion

Abstract: Background. Successful intestinal transplantation is currently hindered by graft injury that occurs during procurement and storage, which contributes to postoperative sepsis and allograft rejection. Improved graft preservation may expand transplantable graft numbers and enhance posttransplant outcomes. Superior transplant outcomes have recently been demonstrated in clinical trials using machine perfusion to preserve the liver. We hypothesized that machine perfusion preservation of intestinal allografts could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent preclinical studies and clinical trials have demonstrated that NMP preserves the liver better than SCS (16)(17)(18). For intestine preservation, NMP was shown to be a viable method for graft preservation (19) and transplantation (20) in porcine transplantation models. HMP technology has been widely used in organ transplantation, particularly kidney transplantation (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical studies and clinical trials have demonstrated that NMP preserves the liver better than SCS (16)(17)(18). For intestine preservation, NMP was shown to be a viable method for graft preservation (19) and transplantation (20) in porcine transplantation models. HMP technology has been widely used in organ transplantation, particularly kidney transplantation (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%